Differentiating math instruction K-8 common core mathematics in the 21st century classroom - Bender, William N. (Thousand Oaks, California Corwin, 2013)
This title blends the best of what technology has to offer with guidelines for meeting the objectives set forth by the common core. Every new innovation in math instruction is addressed: flipping math instruction; project-based learning; using Khan Academy in the classroom; educational gaming; teaching for deeper conceptual understanding
Previous edition: 2009
Title from title screen (viewed October 20, 2023)
Includes bibliographical references and index
Specialized
Description based on print version record
Keywords: Individualized instruction -- United States; Mathematics -- Study and teaching (Elementary) -- United States; Mathematics -- Study and teaching (Middle school) -- United States; Mathematics -- Study and teaching (Preschool) -- United States